Global, regional and national burdens of reproduction-related congenital birth defects, 1990–2019 - Shen, Lin; Li, Jie; Zhang, Hanwang; Zhao, Yiqing (Frontiers in Public Health, 2024)
Background Reproduction-related congenital birth defects (RCBDs), including Klinefelter syndrome (KS), Turner syndrome (TS), and urogenital congenital anomalies (UCA), can lead to severe physical and psychosocial disorders. The global impact of RCBDs on children and adults is unknown, which limits high-quality development of populations and increases in life expectancy per capita. Methods Annual incidence rates, prevalence rates (PR), and disability-adjusted life year (DALY) rates were collected for KS, TS, and UCA for 204 countries and territories, including at birth, for children younger than 1 year, and age-standardized (AS) for all ages. Linear regression was used to calculate their estimated annual percentage changes (EAPCs). Finally, the relationships between EAPCs of each indicator and sociodemographic index (SDI) was investigated using Pearson correlation analysis. Results Globally, the age-standardized prevalence rate (ASPR) trend is decreasing in KS and TS and increasing in UCA. The DALY rates for children younger than 1 year were on a downward trend in KS and UCA, while they were still rising for TS. The AS-DALY rates were all on a downward trend in KS, TS, and UCA. The DALY rates of KS, TS and UCA were found higher in high-income countries in North America. In addition, the burdens of TS and UCA went down with increasing SDI, whereas the burden of KS increased with increasing SDI. Conclusion The global burdens of RCBDs have decreased since 1990. This finding can help policymakers implement cost-effective interventions to reduce the burdens of RCBDs.